Sosialisasi Efisiensi Penggunaan Gadget pada Anak Sekolah Dasar - Dian Riani Said; Muhdar, Fahriadi; Vina Sari, Wilda; Nyala, Asmi; Kamal, Nurhidayah (INCOME: Indonesian Journal of Community Service and Engagement, 2024)
An initial survey in Patangkai Village found that the use of gadgets by elementary school age children was not too worrying. This shows that the use of gadgets has been used by students at the school. The aim of this service is to increase the knowledge and abilities of children in partner environments in knowing the impact of using gadgets. Increasing elementary school age knowledge in an era of technology that is so rapidly used. This service activity is carried out by delivering material to them at their respective schools. The results of service activities are: 1). Participants already know the negative impacts of using gadgets excessively and without supervision from parents or the school. The impact that will be felt is not only on them but also on the family environment. 2). The positive impact of using gadgets is very useful for education and developing their knowledge about the outside world. As a result of this socialization, participants are ready to use gadgets positively and can filter out those that could have a negative impact on them. Kata Kunci : Gadget, School, Student